Geolinguistic Boundaries in International Foreign- Language Textbooks: A Cross-Language Analysis - Orlando, Maximiliano Eduardo (Lenguas Modernas, 2016)
Several studies have reported the quasi-exclusive inclusion of culturalelements of a given country in foreign language textbooks that teach this country’sfirst\second language. This research builds on the findings of these studies bycarrying out cross-language analyses. First, it establishes geolinguistic boundariesin a set of international English as a foreign language textbooks and French as aforeign language textbooks by looking into the frequencies of words that referto geographical places and origins in 1,853 texts. Then, it uncovers the criterialying behind the definition of these boundaries. Indeed, this paper identifies fourgeolinguistic areas in either set of textbooks: a “core target language speakingarea”, an “extended target language speaking area”, a “mutual influence area” anda “remote area”. It also argues that the identification of the contents of these fourgeolinguistic areas in a given international foreign-language textbook would supplyforeign language teaching professionals with information on the conception of thespeaking world of the target language that learners may receive from this textbook.Furthermore, this identification may be useful for finding out whether it containsgeolinguistic areas whose contents match foreign language learners’ learning needsand wants. It may be used to supplement if it includes geolinguistic areas whosecontents are not included.